Perkecambahan dan Perbanyakan Gaharu secara In Vitro - Mia Kosmiatin; Ali Husni; Ika Mariska (Jurnal AgroBiogen, 2005)
Agarwood (Aquilaria malaccensis Lank) is one of the forest wood that are continously exploited. Currently, the Indonesian export of agarwood is decreasing because its population is endangered by excessive logging. Agarwood propagations need technology for reproduction of agarwood seedlings and their fungal inoculum. In vitro technique for germination of recalsitrant seeds and micropropagation are technologies that can be used for propagation of agarwood seedlings. An experiment was done to develop techniques for in vitro germination and micropropagation of agarwood. The in vitro germination was done using two different techniques. Firstly, sterile seeds were germinated on an MS medium + 50 mg/l PVP, 50 mg/l GA, and 1 mg/l BA or kinetin. Secondly, sterile seeds were germinated on basal medium of MS, 1/2 MS medium, MS medium without vitamins, as well as on MS medium without pyridoxine, nicotinic acid and WPM. Shoot initiations and multiplications were done on MS and 1/2 MS media containing 1, 3, or 5 mg/l BA. The explants used were cotyledone nodes, terminal shoots, single node with leaf, and sinle node without leaf. The results showed that the seed germination rate on the different media ranged from 7,14 to 50%. The seed germination rate on the MS medium without vitamis was the highest. The best explants for shoot induction and multiplication was single node with leaf which was cultured on MS + 1 mg/l BA.